Em busca de santidade: os manuscritos do Mar Morto e o modo de vida religiosa dos essênios e dos terapeutas - Araújo Júnior, João Alves de (2012)
This dissertation aims to understand the mode of religious life of the Essenes and Therapeutae through investigating the reason and motivating purpose of such living. The methodological procedure is based on a historical and hermeneutics analysis of texts concerning the object of study. Within the study of Judaism, the relevance of the object of research is justified on the one hand, because the lifestyle of the groups included in Essenism be sui generis, and, on the other hand, the discovery of the Dead Sea Scrolls, which are linked to an Essene character sect, be considered one of the major findings biblical documentary of all time. The analysis of the social, historical and religious context of the Judaism in the Second Temple period shows that in the late phase of this period in the history of the Jewish people, the Jewish nation was influenced by foreign policies that affected the religious sphere. Because of this, Jews interested in defending the principles and values of their religion rebelled against those who wanted to impose Hellenistic customs in the Jewish religious system. It is speculated that this rise may have been one of the factors that led to the formation of religious groups – comprehended in the Essene movement – which understood to be necessary to adopt a peculiar way of life to preserve the rectitude of the Jewish religious living. This righteousness was seen as a holy life based on the determination of the Torah according to the specific interpretation of each sect.